2017
DOI: 10.1186/s12888-017-1497-6
|View full text |Cite
|
Sign up to set email alerts
|

Periodic catatonia with long-term treatment: a case report

Abstract: BackgroundPeriodic catatonia has long been a challenging diagnosis and there are no absolute guidelines for treatment when precipitating factors are also unclear. We report a schizophrenia patient with periodic catatonia with a 15-year treatment course. A possible correlation between decreased daylight exposure and periodic attacks has been observed.Case presentationWe describe a 49-year-old woman with periodic catatonia associated with schizophrenia with 15 years of follow-up. The patient was treated with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
0
4
0
3
Order By: Relevance
“…Older published studies have reported cyclic shifts in nitrogen balance or thyroid dysfunction in association with periodic catatonia 2. Finally, in another case report, Chen and Huang17 noted a correlation between decreased daylight exposure and catatonia attacks, despite the patient’s good adherence to medication.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Older published studies have reported cyclic shifts in nitrogen balance or thyroid dysfunction in association with periodic catatonia 2. Finally, in another case report, Chen and Huang17 noted a correlation between decreased daylight exposure and catatonia attacks, despite the patient’s good adherence to medication.…”
Section: Discussionmentioning
confidence: 90%
“…22 There are also reports on the benefit of clozapine for patients with catatonia, with an increase in the duration of the catatonia-free period reported. 17,23 However, atypical antipsychotics should be used with caution as catatonia is a risk factor for the development of neuroleptic malignant syndrome. 4,7 Other reports have suggested using N-methyl-D-aspartate receptor antagonists, such as amantadine and memantine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is great uncertainty in the treatment of periodic catatonia, though several sources advise treatment in acute catatonic episodes along the lines of other cases of catatonia with benzodiazepines and ECT ( Fink and Taylor, 2001 ; Ghaffarinejad et al, 2012 ; Hervey et al, 2013 ), and several reports support this ( Chen and Huang, 2017 ; Hervey et al, 2013 ; Saddichha et al, 2007 ). However, some cases do not respond to these treatments.…”
Section: Subtypes Of Catatonia and Related Conditionsmentioning
confidence: 99%
“…S obzirom na multifaktorijelnu etiologiju katatonije, kod naše pacijentkinje (biološki faktori, psihološki faktori i psihosocijalni stres) neophodan je integrativni pristup dijagnostici i terapiji prema redu hitnosti i težini kliničke slike, a nakon produženog stacionarnog lečenja smatramo indikovanim redovne kontrole psihijatra, uz medikamentoznu terapiju i psihoterapijsku podršku jednom nedeljno (suport i kognitivnobihejvioralna terapija -KBT), kao i terapiju zbog politoksikomanije [19][20][21].…”
Section: Diskusijaunclassified